2017
DOI: 10.3389/fninf.2017.00029
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Phrase Rhythm: An EEG Study of Bipartite vs. Rondo Sonata Form

Abstract: This paper introduces the neural correlates of phrase rhythm. In short, phrase rhythm is the rhythmic aspect of phrase construction and the relationships between phrases. For the sake of establishing the neural correlates, a musical experiment has been designed to induce music-evoked stimuli related to phrase rhythm. Brain activity is monitored through electroencephalography (EEG) by using a brain–computer interface. The power spectral value of each EEG channel is estimated to obtain how power variance distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…EEG connectivity features were reported to play an essential role in the recognition tasks [37]. Another study, using the same device, observed a correlation of EEG with classical music rhythm [38], [39]. Music therapy is one of the applications emanating from music-elicited emotion [40].…”
Section: Consumer Grade Eeg For Emotion Recognitionmentioning
confidence: 98%
“…EEG connectivity features were reported to play an essential role in the recognition tasks [37]. Another study, using the same device, observed a correlation of EEG with classical music rhythm [38], [39]. Music therapy is one of the applications emanating from music-elicited emotion [40].…”
Section: Consumer Grade Eeg For Emotion Recognitionmentioning
confidence: 98%
“…Information that identifies a user' affective states is used to adapt the behavior of an application to keep the user satisfied or engaged. For example, some studies found neurophysiological responses in theta and alpha frequency bands to differentiate between episodes of frustrating and normal game play (Shergill et al, 2013 ) or even musical emotion regulation (Fernández-Sotos et al, 2016 ; Martínez-Rodrigo et al, 2017 ).…”
Section: Most Important Challenges In Human-avatar Symbiosis For Amentioning
confidence: 99%
“…Electroencephalographic techniques find applications in adult psychiatry (Sand et al, 2013 ). Electrophysiological methods have developed in recent decades (Kamarajan and Porjesz, 2015 ; Martínez-Rodrigo et al, 2017 ). Recently there has been a rapid advance in therapeutic use of Brain-Computer Interfaces (BCI) in which the acquisition of electrical activity of selected areas of brain cortex plays the main role (Mikołajewska and Mikołajewski, 2012 , 2013 , 2014 ; Teruel et al, 2017 ) and Event-Related Potentials (ERP) and other evoked potentials can lead not only to explanation of psychological behaviors in particular situations (Kotyra and Wojcik, 2017a , b ) but also to finding some biomarkers characteristic of psychiatric disorders (Chapman and Bragdon, 1964 ; Sutton et al, 1965 ; Campanella, 2013 ; Golonka et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%